A Five Year financial plan for JoTech Packaging Corporation - Clemente, Airitz Vida F. et. al. 4 0 16; 5 (2018)
EXECUTIVE SUMMARY: This report provides an analysis and evaluation of the current prospective profitability, liquidity and financil stability of Phil-Nippon Kyoel Corp. Methods of analysis include trend, horizontal and vertical analysis as well as ratios such as leverage, growth potential and efficiency ratios. Other calculations include rates of return on Shareholder's Equity and Total Assets and Debt to equity to name a few. All calculations can be found in the appendices. The Phil-Nippon Kyoei Corp. Is a SEC registered company founded by Filipino and Japanese engineers in 1995. Its mission is to spread the operational practice that planned engineering maintenance, strategic materials procurement and equipment performance monitoring are occassions to improve returns and business profits. PNKC is a holding company of strategic business units engaged in industrial trading, technical consultancy, pwer and energy, shipping maintenance and operations, and cold storage and logistics services. Since its incorporation, PNKC has established solid business relationships with companies belonging to the top 1000 Philippine corporations for all its related businesses. Technomarine Co. Ltd., a company based in Kobe, Japan, owns 40% of the total equity of PNKC.
Financial Planning: (BSBA major Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2